Quality Management of Facilities and Infrastructure within the Postgraduate Program at UIN Maulana Malik Ibrahim Malang - Akbar, Yusuf; Harnika, Lika; Wulandari, Sri; Fikri, Shofil (Abjadia : International Journal of Education, 2025)
The quality management of facilities and infrastructure needs to be well understood. The quality of learning can also be determined by the effectiveness of facilities and infrastructure management. This study identifies the issue of how the quality management process of facilities and infrastructure is carried out within the postgraduate environment of UIN Maulana Malik Ibrahim Malang. This study aims to provide knowledge about the stages of quality management of facilities and infrastructure in the theory of Purwasih & Sahnan (2022) and to explore the process of quality management of facilities and infrastructure in the postgraduate environment of UIN Maulana Malik Ibrahim Malang. This type research is field-based qualitative research. Data collection techniques include observation, interviews, and documentation. The primary data sources were interviews with two informants, namely the head of administration and the financial manager, as well as documents on facilities and infrastructure at the Postgraduate Program of UIN Maulana Malik Ibrahim Malang. Secondary data sources are obtained from books, journals, and scientific articles related to quality management of facilities and infrastructure. The findings show that the postgraduate program of UIN Maulana Malik Ibrahim Malang carries out management processes for facilities and infrastructure through planning, procurement, distribution, maintenance, disposal, and supervision of items such as projectors, whiteboards, LCD TVs, desks, chairs, buildings and classrooms, libraries, laboratories, and others. These processes are carried out Purwasih and Sahnan (2022) framework of facilities and infrastructure quality management. From these findings, it can be understood what units are needed and how the implementation process of quality management of facilities and infrastructure is conducted in the higher education environment.